Trajectories of productivity loss over a 20-year period: an analysis of the National Longitudinal Survey of Youth - Elyssa Besen; Glenn Pransky (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: We investigated multiple trajectories of the probability of reporting health-related productivity loss over a 20-year period among adults aged 25-44 years and explored differences among the trajectories in demographic and personal characteristics and employment outcomes in midlife. METHODS: A latent class growth analysis of health-related productivity loss was estimated on 12 waves of data from the National Longitudinal Survey of Youth (NLSY79) (N=5699), an ongoing nationally representative longitudinal survey of Americans. Waves 1-5 were collected annually at ages 25-29 years. Waves 6-12 were collected biennially at ages 30-44 years. Productivity loss was measured as "health fully preventing a person from working" or "health limiting the amount of kind of work a person could do". Differences among trajectories were assessed using analyses of variance (ANOVA) and Chi-square tests. RESULTS: A five-group trajectory model for productivity loss was identified: (i) no risk, (ii) low risk, (iii) high risk, (iv) increasing risk at early ages, and (v) increasing risk at later ages. At the first wave, after the waves used for the trajectory model in which respondents were approximately age 45 years, the no- and low-risk groups worked the most weeks and hours per week and had the highest percentages of participants employed ≥10 weeks compared to the high-risk and early-/late-onset increasing-risk groups, all of which had the lowest levels of mastery, self-esteem, education, and socioeconomic status. CONCLUSIONS: There are several developmental patterns of productivity loss, with some trajectories being associated with lower work participation in midlife. These high risk patterns may be indicative of individuals needing intervention to prevent premature work withdrawal.